Comparison between active dry yeast and fresh compressed yeast on activation temperature / Amiera Ardilla Azmi - Azmi, Amiera Ardilla (Faculty of Applied Sciences, 2015)
A study has being conducted on two forms of yeast; Active Dry Yeast (ADY) and Fresh Compressed Yeast (FCY). The study aim is to investigate and compare the effect of different forms of yeast on activation temperature. Both forms of yeast were activated using different water temperature. Yeast activity was being studied by using balloon inflation technique. The higher the diameter of balloon, more carbon dioxide was being produced and more active yeast was. As the indicator for yeast activity, dough expansion was measured and the firmness of resulted bread was analyzed by texture analyzer. This present study showed that the ranges of activation temperature for ADY and FCY were from 25 - 55˚C and 35 - 55˚C respectively. Additionally, the highest dough expansion of ADY and FCY were found at 30˚C and 38˚C correspondingly. Furthermore, the lowest firmness of ADY and FCY bread were found at 35˚C and 38˚C individually. It can be concluded that ADY was less sensitive to temperature compared to FCY as ADY has a wider ranges of activation temperature.